The Research,Industry, Community, Alumni, Entrepreneurship, and Network (RICAEN) unit at UiTM - Norzan, Nurul Hanis (Universiti Teknologi MARA, Perlis, 2024)
The Industrial Training Program is a comprehensive initiative designed to prepare participants for success in the dynamic industrial landscape. With a focus on bridging the gap between academic theory and practical application, the program offers a unique blend of direct training, industry mentorship, and collaborative projects. I am gaining valuable insights into various industrial domains, from manufacturing to technology, thereby enhancing their skill sets and employability. This experience enables me to learn something new while gaining a deeper understanding of the realities of the job. Industrial training is a mandatory requirement for all students to graduate. Consequently, I completed my industrial training at the Research, Industry, Community, Alumni, Entrepreneurship, and Network unit at UiTM Perlis from October 16, 2023, to February 23, 2023. Throughout this term of industrial training, I discovered that the knowledge acquired at university is often insufficient. During my internship at there, I was assigned to the research management unit, with DR Muhammad Faiz Pa’suya my supervisor, who serves as the research management coordinator. Assisting me in my tasks was Puan Zurita Jaafar, also a member of the research management team. RICAEN plays a crucial role at UiTM, managing industrial collaborations between UiTM Perlis and other local or international universities. The program includes immersive firsthand experiences with industry standard equipment, mentorship from seasoned professionals, and the completion of real-world projects. The emphasis on workplace ethics, communication, teamwork, and leadership skills ensures that participants not only acquire technical proficiency but also develop the soft skills necessary for thriving in a professional environment. This report encompasses what I have learned, the company's background information, training reflection, and a SWOT analysis of the company. During my time there, I identified some of the company's weaknesses, strengths, threats, and opportunities, which will be discussed further in this report. Finally, I provide several recommendations, elaborated upon in subsequent sections of this report.